Pengaruh Kompensasi Dan Motivasi Terhadap Kinerja Karyawan Pada Koperasi Pegawai Negeri Universitas Hasanuddin Makassar - Nini Karlina; Andi Irfan; Baharuddin Baharuddin (Ebisnis Manajemen, 2023)
This research aims to determine the influence of compensation and motivation on employee performance at the Hasanuddin University Makassar Civil Servant Cooperative which operates in the field of funding and financing product needs. The data used in this research is primary data with a sampling method using saturated sampling, and a data analysis method using multiple linear analysis, while the sample taken was 50 employees. The results of this research have been tested for validity and reliability, and have also been tested. The data analysis method uses multiple linear regression analysis techniques and hypothesis testing. The results of this research show that the Compensation variable (X1) has a positive and significant effect on employee work (Y). This means that providing increased compensation to employees will improve employee performance and motivation (X2) has a positive and significant effect on employee work (Y) at the Hasanuddin University Makassar Civil Servant Cooperative. This means that increasing employee work motivation will also increase the performance of employees of the Hasanuddin University Makassar Civil Servant Cooperative.